Out of Modernity: The Search for Identity in Study Abroad and Performance of Identity in Cultural Tourism - Eaton, Jacob Copeland (Tufts Archival Research Center, 2005)
This paper explores the boundaries of anthropology, edu-tourism and study abroad. It illustrates how the cultural interactions in both study abroad experience and in cultural tourism adhere to roles dictated by mass media. It goes on to explore how the performance of identity in East African cultural tourism, despite adhering to the tourist gaze of Western thought, allows indigenous tribes with cultural, political and economic autonomy. The first chapter surveys the anthropological thought on tourism and provides a background of tourism in Kenya and Tanzania. The second chapter looks at the growing field of Maasai tourism in Kenya. The third chapter examines the issue of land rights for the hunter-gatherer Hadzabe of Tanzania and how tourism allows the group a measure of control over their land. The final chapter looks at what students make of the study abroad experience, and how program design and norms influence what students take away from their time overseas.